Do salt marshes survive sea level rise? Modelling wave action, morphodynamics and vegetation dynamics. (November 2018) - Best, Ü.S.N.; Van der Wegen, M.; Dijkstra, J.; Willemsen, P.W.J.M.; Borsje, B.W.; Roelvink, Dano J.A.
Abstract: This paper aims to fundamentally assess the resilience of salt marsh-mudflat systems under sea level rise. We applied an open-source schematized 2D area model (Delft3D) that couples intertidal flow, wave-action, sediment transport, geomorphological development with a population dynamics approach including temporal and spatial growth of vegetation and bio-accumulation. Wave-action maintains a high sediment concentration on the mudflat while the tidal motion transports the sediments within the vegetated marsh areas during flood. The marsh-mudflat system attained dynamic equilibrium within 120 years. Sediment deposition and bio-accumulation within the marsh make the system initially resilient to sea level rise scenarios. However, after 50–60 years the marsh system starts to drown with vegetated-levees being the last surviving features. Biomass accumulation and sediment supply are critical determinants for the marsh drowning rate and survival. Our model methodology can be applied to assess the resilience of vegetated coast lines and combined engineering solutions for long-term sustainability. Graphical abstract: Image 1 Highlights: Realistic marsh-mudflat system in near equilibrium within a century (Video 2.6 ). Wave action is the primary trigger for sediment supply to the mudflat. The marsh-mudflat system drowns under sea level rise scenarios. Drowning depends on spatially and temporally varying morphology.